Sen1, the homolog of human Senataxin, is critical for cell survival through regulation of redox homeostasis, mitochondrial function, and the TOR pathway in Saccharomyces cerevisiae. (24th October 2016) - Sariki, Santhosh Kumar; Sahu, Pushpendra Kumar; Golla, Upendarrao; Singh, Vikash; Azad, Gajendra Kumar; Tomar, Raghuvir S.
Abstract : Mutations in the Senataxin gene, SETX are known to cause the neurodegenerative disorders, ataxia with oculomotor apraxia type 2 (AOA2), and amyotrophic lateral sclerosis 4 (ALS4). However, the mechanism underlying disease pathogenesis is still unclear. The Senataxin N‐terminal protein‐interaction and C‐terminal RNA/DNA helicase domains are conserved in the Saccharomyces cerevisiae homolog, Sen1p. Using genome‐wide expression analysis, we first show alterations in key cellular pathways such as: redox, unfolded protein response, and TOR in the yeast sen1 ΔN mutant (N‐terminal truncation). This mutant exhibited growth defects on nonfermentable carbon sources, was sensitive to oxidative stress, and showed severe loss of mitochondrial DNA. The growth defect could be partially rescued upon supplementation with reducing agents and antioxidants. Furthermore, the mutant showed higher levels of reactive oxygen species, lower UPR activity, and alterations in mitochondrial membrane potential, increase in vacuole acidity, free calcium ions in the cytosol, and resistance to rapamycin treatment. Notably, the sen1 ∆N mutant showed increased cell death and shortened chronological life span. Given the strong similarity of the yeast and human Sen1 proteins, our study thus provides a mechanism for the progressive neurological disorders associated with mutations in human senataxin. Abstract : Mutations in the gene encoding senataxin are associated with neurodegenerative disorders, but the mechanism by which mutant senataxin contributes to neurodegeneration is unclear. To shed light on this issue, Tomar et al . investigated the functional effects of mutations in Sen1, the yeast orthologue of senataxin. Loss of the conserved N‐terminal domain of Sen1 deregulated ER, lipid and redox homeostasis; modulated the TOR signalling pathway and autophagy; induced mitochondrial and peroxisomal dysfunction; increased cell death and shortened the chronological life span. These results suggest that senataxin might have a key role in cellular homeostasis that underpins its function in neurodegeneration.